2015
DOI: 10.3109/08941939.2015.1024357
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Nitric Oxide on Liver Circulation from Ischemia Reperfusion Injury

Abstract: Regional administration of SNP into the portal vein increases hepatic arterial flow during ischemia reperfusion periods without altering mean systemic arterial pressure. We speculate that administration of an exogenous NO donor may be effective in preventing liver injury via preservation of total hepatic blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It can interfere with the production of nitric oxide by l -arginine [ 43 ]. Previous studies found that the reduction of endogenous nitric oxide (NO) can lead to liver injury [ 44 ]. Our study found that this metabolite increased with the progress of S. japonicum infection, and it may aggravate liver injury by reducing the synthesis of nitric oxide in their bodies.…”
Section: Discussionmentioning
confidence: 99%
“…It can interfere with the production of nitric oxide by l -arginine [ 43 ]. Previous studies found that the reduction of endogenous nitric oxide (NO) can lead to liver injury [ 44 ]. Our study found that this metabolite increased with the progress of S. japonicum infection, and it may aggravate liver injury by reducing the synthesis of nitric oxide in their bodies.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the xenobiotic attack, the liver that was regenerating post-injury provides a model of cell proliferation to research the cause of the cell division modulation [ 42 , 43 , 44 ]. After cell loss in hepatotoxins induced tissue injury, the liver of mammals has been shown to possess the capacity to grow [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the accumulation of intestinal toxins in the liver also increases ET levels. However, NO acts as a main antagonist of NO and is down-regulation during ischemia (Toshihiro et al 2015). ET can act on hepatic sinusoids, resulting in the stenosis of the liver sinusoid.…”
Section: Discussionmentioning
confidence: 99%